2016
DOI: 10.1016/j.fertnstert.2016.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Stanniocalcin-1 expression in normal human endometrium and dysregulation in endometriosis

Abstract: Objective To determine expression of stanniocalcin-1 (STC1) in human endometrium with and without endometriosis and its regulation by steroid hormones. Design Laboratory study. Setting University. Patients 19 women with endometriosis and 33 control women. Intervention(s) Endometrial biopsy and fluid sampling Main Outcome Measure(s) Analysis of early secretory (ESE) and mid-secretory (MSE) endometrial secretomes from fertile women with nano-LC/MS/MS; real-time Q-PCR and immunohistochemistry for STC1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…In line with recent data on STC-1 expression in the normal human endometrium, our findings indicate that the endometrial epithelium is the main target of STC-1 localization, while the stroma is not ( 43 , 44 ). This also applies to hormone-dependent tumor tissues like breast and ovarian cancers underlying the role of STC-1, especially in adenocarcinoma development ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 92%
“…In line with recent data on STC-1 expression in the normal human endometrium, our findings indicate that the endometrial epithelium is the main target of STC-1 localization, while the stroma is not ( 43 , 44 ). This also applies to hormone-dependent tumor tissues like breast and ovarian cancers underlying the role of STC-1, especially in adenocarcinoma development ( 17 , 18 ).…”
Section: Discussionsupporting
confidence: 92%
“…Although the effect of cAMP in regulating STC‐1 mRNA expression has been studied, the effect is tissue specific. In human endometrial stromal cells and rat neuroblastoma cells, cAMP stimulates STC‐1 expression . However, in rat Sertoli and Leydig cells the opposite effect was observed .…”
Section: Discussionmentioning
confidence: 96%
“…Other pregnancy-related studies showed strong expression of stanniocalcin (STC) 1 and STC2 mRNA in decidualized rat cells, suggesting that STC1 and STC2 play important roles in implantation and decidualization (75). In humans, STC1 is upregulated in the secretory endometrium compared with that in the proliferative endometrium, and is dysregulated in the eutopic endometrium of patients with endometriosis, suggesting its roles in the pathogenesis of decidualization defects (76). Therefore, accumulating evidence indicates that the WDFY3-AS2/miR-135a/STC1 axis may be involved in endometrial stromal cell decidualization.…”
Section: Discussionmentioning
confidence: 99%